Implementation of Religious Moderation Education in Strengthening the Religiosity of Elementary School Students: A Study on the Religious Sleman Program - Dewi Widiyastuti; Arif Rahman (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Strengthening religious moderation in basic education is a strategic need amid the increasing phenomenon of religious intolerance and exclusivism in the younger generation. This study aims to analyze the implementation of religious moderation education through the Religious Sleman Program at SD Negeri Model Ngemplak and assess its effectiveness in developing students' religiosity. The research uses a qualitative approach with a descriptive type. Data was obtained through observations, in-depth interviews, and documentation involving school principals, interfaith teachers, students, and religious education supervisors. Data analysis was carried out using the Miles and Huberman model through data reduction, data presentation, and conclusion drawn, with validity tests through triangulation of sources, techniques, and time. The results of the study show that the implementation of religious moderation is carried out through the integration of values in learning, daily religious habits, strengthening inclusive school culture, and interfaith collaboration. The program is effective in shaping students' religiosity that is not only ritualistic, but also reflects a tolerant, empathetic, and respectful attitude toward diversity. The obstacles found include the limited understanding of some teachers about the concept of moderation and the lack of optimal continuous evaluation system. This study concludes that religious moderation education in primary schools plays a significant role in building the religious-moderate character of students and requires strengthening the capacity of educators and sustainable policy support.